For speaking excellently in their language: interpreters in Carmen de Patagones (1779-1783) (Quinto Sol, 2026)
This work studies the role played by interpreters as cultural mediators in the first four years of Carmen de Patagones' existence, enclave created by the Spanish Crown at the mouth of the Rio Negro, south of the capital of the Viceroyalty of the Rio de la Plata. The trajectories of four of them were followed, to analyze their personal backgrounds through mostly unpublished sources. We pay attention to the conditions and ways of learning native languages in a context of captivity, focusing especially on the conditions that a reliable interpreter —go-between— had to meet from the perspective of their clients.
Keywords: captives; intermediaries; interpreters; interethnic relations